Particle Integrity and Size Effect on the Journey of Polymeric Nanocarriers in Zebrafish Model and the Correlation with Mice. Issue 43 (16th September 2021) - Tao, Jinsong; Wei, Zhengjie; Xu, Meng; Xi, Long; Cheng, Yaxin; Lee, Simon Ming‐Yuen; Ge, Wei; Zheng, Ying
Abstract: Polymeric nanocarriers have high biocompatibility for potential drug delivery applications. After entering bloodstream, nanocarriers will circulate, interact with proteins, dissociate, or be cleared by reticuloendothelial system. Zebrafish as a visual animal model, can serve as a tool for screening nanomedicines and monitoring nanocarrier behaviors in vivo. However, a comprehensive correlation between zebrafish and rodent models is currently deficient. Here, different‐sized poly(caprolactone) nanocarriers (PCL NCs) are fabricated with or without PEGylation to investigate correlation between zebrafish and mice regarding their biofate via Förster resonance energy transfer technique. Results show that PEGylated PCL NCs have higher integrity in both zebrafish and mice. Small PEG‐PCL NCs have longer circulation, while large PEG‐PCL NCs have dramatically higher macrophage sequestration in zebrafish and mice spleen, leading to poor circulation. PCL NCs dissociate rapidly with less macrophage sequestration. Moreover, in 7 days postfertilization (dpf) zebrafish, polymers are eliminated via hepatobiliary pathway, which is not fully functional at earlier stages of development. The effects of nanocarrier integrity on macrophage sequestration in zebrafish and good correlation with mice spleen are pioneered to be demonstrated. The findings suggest that 7 dpf zebrafish are suitable as an in vivo screening model of nanocarriers and predict their biofate in rodents. Abstract : The 7 days postfertilization (dpf) zebrafish combining with Förster resonance energy transfer technique demonstrate the particle integrity and size effect on the journey of polymeric nanocarriers in vivo and correlate well with their biofate in mice. This 7 dpf zebrafish are suitable as an in vivo screening model in early preclinical study of nanocarriers and predict their biofate in rodents.